ANALYSIS OF THE EFFECT OF LEADERSHIP STYLE, DISCIPLINE, AND MOTIVATION ON EMPLOYEE PERFORMANCE IN PT RIMBA KENCANA MALANG - Susilo, Sony Wicaksono; Manalu, Sahala (Jurnal Aplikasi Manajemen, 2017)
Retaining job satisfaction and organizational commitment are the most usual problems faced by a company. The purpose of this research is to answer the impact of job satisfaction on turnover intention, impact of organizational commitment on turnover intention, and impact of job satisfaction on turnover intention through organizational commitment as intervening variable. The sample used was employees of Swiss-Belinn Malang; the number of samples specified in this study is 25 respondents who are employees at the Back of House (BOH).The method used in this sampling is to use census questionnaire instrument used to collect research data, while the data analysis method used is multiple linear regression analysis, by using SPSS. The test results of the hypothesis show that job satisfaction has a positive and significant impact on the variable of employee turnover intention in Swiss-Belinn Malang. Organizational commitment results show positive and significant impact on employee turnover intention. Job satisfaction has an effect on turnover intention through organizational commitment. In this study, organizations are able to mediate full commitment (full mediation) the relationship between job satisfaction on employee's turnover intention in Swiss-Belinn. To avoid turnover intention, the Swiss- Belinn need to maintain employee satisfaction by providing facilities that can be enjoyed employees create a harmonious working environment between the employee and the employer and the company should pay more attention to the work of employees with recognition of the results of his work. Swiss-Belinn Hotel needs to maintain the organizational commitment by the company to impose sanctions if the employee resigns before the agreed time period.